Foraminiferal assemblage from estuarine deposits of the Iguape Bay, Bahia Brazil - Machado, Altair De Jesus; Andrade, Edilma De Jesus; Carvalho, José Bites De (Anuário do Instituto de Geociências, 2006)
Abstract